2019
DOI: 10.1080/0284186x.2019.1631476
|View full text |Cite
|
Sign up to set email alerts
|

Survival after stereotactic radiotherapy in patients with early-stage non-small cell lung cancer

Abstract: Introduction: Stereotactic radiotherapy (SBRT) is the treatment of choice for inoperable early stage non-small cell lung cancer (NSCLC). We report analyses of the influence of age on survival after SBRT. Methods and material: From 2005 to 2017, 544 previously un-irradiated patients with early stage NSCLC had SBRT. The data were analyzed in four age groups: A:-69 (176 pts), B: 70-74 (115 pts), C: 75-79 (131 pts) and D: 80 years or older (122 pts). Two SBRT dose regimes were used: 45 Gy/3F (N ¼ 103) and 66 Gy/3F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…The 3-year CSS and DFS rates in the present study were also close to those of patients treated with surgery [25] . In multivariate analysis, we found that good general condition and female gender were correlated with better overall survival as in previous studies [26] . However, no parameter was independently significant for CSS or DFS.…”
Section: Discussionsupporting
confidence: 84%
“…The 3-year CSS and DFS rates in the present study were also close to those of patients treated with surgery [25] . In multivariate analysis, we found that good general condition and female gender were correlated with better overall survival as in previous studies [26] . However, no parameter was independently significant for CSS or DFS.…”
Section: Discussionsupporting
confidence: 84%
“…Stereotactic body radiation therapy (SBRT) has played a crucial role in lung cancer treatment and shown efficient local control according to reported outcomes. [1][2][3][4] The success of lung SBRT relies on the accuracy of treatment delivery. The respiratory motion of the lung tumor poses a significant challenge in SBRT and is considered one of the largest sources of uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…3 Hansen et al reported that the overall survival in 544 inoperable patients with early NSCLC treated with SBRT was 43.9 months, and the 5-year OS was the highest (45%) for patients under 70 years of age. 4 Pooled data from two independent randomized phase 3 trials of SBRT in patients with operable stage I NSCLC versus lobectomy demonstrated 3-year survival rates of 95% versus 79% in the SBRT and lobectomy groups, respectively. 5 These studies show that a number of patients survive for longer periods of time and may experience detrimental long-as well as short-term effects of RT.…”
Section: Introductionmentioning
confidence: 99%